The role of breeding system in community dynamics: Growth and mortality in forests of different successional stages. Issue 15 (27th June 2018) - Wang, Yunyun; Freckleton, Robert P.; Wang, Bojian; Kuang, Xu; Yuan, Zuoqiang; Lin, Fei; Ye, Ji; Wang, Xugao; Hao, Zhanqing
Abstract: Plant sexual systems appear to play an important role in community assembly: Dioecious species are found to tend to have a higher propensity to colonize communities in early successional stages. Here, we test two demographic hypotheses to explain this pattern in temperate forests. First, we test demographic differences between hermaphrodite and dioecious species in stressful younger successional stages: Previous theory predicts that hermaphrodite seed production is more harmed in stressful environments than that of dioecious populations leading to an advantage for females of dioecious species. Second, in primary forest, we hypothesized that dioecious species would show demographic advantage over monomorphic ones. We used data from two temperate forest plots in Northeast China surveyed over 10 years to compare the rates of growth and mortality of tree species with contrasting breeding systems in both secondary and primary forests. We assessed the effect of breeding system on the growth‐mortality trade‐off, while controlling for other traits usually considered as correlates of growth and mortality rates. We show that in the secondary forest, dioecious species showed weak advantage in demographic rates compared with monomorphic species; dioecious species showed considerably both lower relative growth and mortality rates compared to the hermaphrodites in the primary forest over 10 years, consistent with a priori predictions. Hermaphrodites showed strong growth‐mortality trade‐offs across forest stages, even when possibly confounding factors had been accounted for. These results suggest that sexual system influences community succession and assembly by acting on the rates of growth and mortality, and the trade‐off between them. As vegetation develops, the demographic differences between breeding systems are much larger. Our results demonstrate the association between breeding system, succession, and community assembly and that this relationship is succession‐stage dependent. Our findings support the suggestion that the demographic advantage of dioecious species facilitates the coexistence of sexual systems in primary forest. Abstract : This is the first study to relate community assembly during community succession to differences in breeding system in natural forests. We test hypotheses for the growth‐mortality dynamics of trees with contrasting breeding systems across successional stages, revealing that the demographic differences between breeding systems are much larger as succession proceeds.